Antigenic specificities of several Indian stocks of Trypanosoma evansi by Western blot analysis - SINGH, VEER; SINGH, AJIT; CHHABRA, M B (The Indian Journal of Animal Sciences, 2013)
Western blotting was used in the analysis of major antigens in.the whole cell lysate (WCL) preparations of7 stocks of Trypanosoma eyansi isolated from buifaloes, equids and camels from different localities of northern India. Most of the major polypeptides (in sodium dodecyl sulphate polyacrylamide gel electrophoresis) were detected as major antigens employing homologous as well as heterologous hyperimmune sera (HIS). The total number of major antigens detected ranged between 17 to 30, most of which were in the M. W. range of 14.6 to 99.5. Homologous HIS detected more antigens in 5 stocks than the number by heterologous HISÂ· The observation in stock-3 and stock-7 was somewhat different, heterologous HIS detecting more antigens than those by homologous HIS. Antigenic profiles of the WCL did not show resemblance between any 2 of the 7 stocks. Antigenic cross-reactivity ofthe most prominent polypeptide, that presumably represents the major variable surface glycoproteins (VSG) was very high indicating the possibility of single or a few iso-VAT (variable antigen type) population in these 7 stocks.